2012
DOI: 10.1119/1.4731618
|View full text |Cite|
|
Sign up to set email alerts
|

An item response curves analysis of the Force Concept Inventory

Abstract: Several years ago, we introduced the idea of item response curves (IRC), a simplistic form of item response theory (IRT), to the physics education research community as a way to examine item performance on diagnostic instruments such as the Force Concept Inventory (FCI). We noted that a full-blown analysis using IRT would be a next logical step, which several authors have since taken. In this paper, we show that our simple approach not only yields similar conclusions in the analysis of the performance of items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(104 citation statements)
references
References 9 publications
6
96
0
2
Order By: Relevance
“…Similarly, if we evaluate and unify the systematic error from the validation of the distractor and the context [8][9][10][11], we could derive the systematic error of the FCI, thereby allowing us to compare the results considering these inadequacies without modifying them and to effectively measure the effect of physics education. This conclusion would enable our study to provide a positive and far-reaching effect in the field of physics education research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, if we evaluate and unify the systematic error from the validation of the distractor and the context [8][9][10][11], we could derive the systematic error of the FCI, thereby allowing us to compare the results considering these inadequacies without modifying them and to effectively measure the effect of physics education. This conclusion would enable our study to provide a positive and far-reaching effect in the field of physics education research.…”
Section: Discussionmentioning
confidence: 99%
“…For future work, we plan to carry out the qualitative analysis of actual answer choices and patterns as well as quantitative analysis such as item response curves [9,10]. Moreover, we plan to disambiguate our data in order to assess the false-positive ratios by major area and analyze whether they differ among these populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of the items had difficulty parameters outside of the desired range (items 1, 6, and 12 with P > 0.8 and items 17 and 26 with P < 0.2), with none having discrimination less than 0.2. Morris et al reported the item averages of 4500 students pooling data from multiple institutions and reported FCI items 5, 17, and 26 with P < 0.2, but no items with P > 0.8 [5]. Osborn Popp, Meltzer, and Megowan-Romanowicz reported FCI item level scores for 4775 high school students.…”
Section: Difficulty and Discriminationmentioning
confidence: 99%
“…The Force Concept Inventory (FCI) [1] has been studied using tools such as factor analysis [2,3], item response theory [4,5], and network analysis [6]. Though these investigations have probed the structure and validity of the test, they have primarily treated student data as a single undifferentiated sample and have not studied gender effects.…”
Section: Introductionmentioning
confidence: 99%